AMERICAN SOCIETY AFTER WORLD WAR II AND THE LITERARY REPRESENTATION OF ALIENATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines how post-World War II American society produced new literary forms of alienation. The study argues that alienation in post-war American prose was not merely a private psychological condition, but a response to historically specific social pressures: Cold War anxiety, bureaucratic expansion, racial exclusion, suburbanization, and the rise of mass consumer culture. Using qualitative socio-literary analysis, the article considers the cultural background of the period alongside selected works by J. D. Salinger, Ralph Ellison, Saul Bellow, Sloan Wilson, and Joseph Heller. The results show that post-war fiction transformed alienation into a central narrative principle through isolated protagonists, fragmented moral perception, resistance to institutional norms, and a persistent crisis of self-definition. The discussion demonstrates that American literary alienation differs from purely philosophical existentialism because it is mediated through concrete social structures: the school, the corporation, the army, the city, and the racial order. The article concludes that post-war American literature converted the problem of alienation into a cultural diagnosis of a society outwardly prosperous but inwardly unstable.